2017
DOI: 10.1016/j.aca.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

A FTIR/chemometrics approach to characterize the gamma radiation effects on iodine/epoxy-paint interactions in Nuclear Power Plants

Abstract: The effects of radiation on polymeric materials are a topic of concern in a wide range of industries including the sterilization, and the nuclear power industry. While much work has concentrated on systems like polyolefins that are radiation sterilized, some work has been done on epoxy systems. The epoxy system studied is an epoxy/amine paint which is representative of the paint that covers the inner surfaces of the French nuclear reactor containment buildings. In case of a severe accident on a Nuclear Power P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…FPDMS was formed after a ring opening reaction. On the spectra, we observed the disappearance of the oxirane ring and the appearance of a C-O characteristic absorption peak at 1107 cm -1 [15]. These results revealed that the ring opening reaction was successful.…”
Section: Results and Discussion 31 Characterization Of Si-pu/apts-gpmentioning
confidence: 73%
See 1 more Smart Citation
“…FPDMS was formed after a ring opening reaction. On the spectra, we observed the disappearance of the oxirane ring and the appearance of a C-O characteristic absorption peak at 1107 cm -1 [15]. These results revealed that the ring opening reaction was successful.…”
Section: Results and Discussion 31 Characterization Of Si-pu/apts-gpmentioning
confidence: 73%
“…As shown in Fig. 3, the characteristic absorption peak of CH2 stretching on the APTS spectrum appeared at 3050-2800 cm -1 [15,20], and those of N-H, Si-O-C, and Si-OEt were at 1640-1550 cm -1 [21][22], 1200-1000 cm -1 [23], and 1180 cm -1 [24], respectively. Moreover, the characteristic absorption peak of the oxirane ring group on the GPTS spectrum was at 910 cm -1 [13][14].…”
Section: Results and Discussion 31 Characterization Of Si-pu/apts-gpmentioning
confidence: 85%
“…A peak was found at 1730 cm −1 for CO stretching vibrations as an outcome of the solvent effect. Additionally, the new peak observed at 1600 cm −1 was probably due to CC stretching . A peak was found at 1640 cm −1 for the CC bond of benzene rings in LABSA .…”
Section: Resultsmentioning
confidence: 81%
“…Additionally, the new peak observed at 1600 cm −1 was probably due to C C stretching. 33 A peak was found at 1640 cm −1 for the C C bond of benzene rings in LABSA. 33 The signal at 1040 cm −1 indicates the S O bond of the sulfonic groups of LABSA.…”
Section: Impact Strengthmentioning
confidence: 96%
“…FPDMS was formed after a ring opening reaction. In the spectra, we observed the disappearance of the oxirane ring and the appearance of a C-O characteristic absorption peak at 1107 cm −1 [16]. These results reveal that the ring opening reaction was successful.…”
Section: Resultsmentioning
confidence: 95%